2018
DOI: 10.1021/acs.orglett.8b02757
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed [3 + 2] Cycloaddition Reaction of α-Diazoacetates and β-Trifluoromethyl Enones: A Facile Access to Multisubstituted 4-(Trifluoromethyl)pyrazolines

Abstract: A novel phosphine-catalyzed [3 + 2] cycloaddition of α-diazoacetates and β-trifluoromethyl enones has been developed that provides facile access to multisubstituted 4-(trifluoromethyl)pyrazolines in good to excellent yields at room temperature. In addition, a tandem [3 + 2] cycloaddition/Michael addition is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…Diazocarbonyl compounds have been versatile intermediates in diverse organic syntheses that can easily generate electron-deficient metal carbenes (Scheme A, I) in the presence of transition metal catalysts and further undergo a number of chemical transformations such as cyclopropanation, X–H (X = C, O, S, or N) insertion, ylide formation, and formal carbene dimerization . In addition, Lewis base catalysis was reported to promote (3+2) cycloaddition of nucleophilic diazocarbonyls activated by triphenylphosphine to react with β-trifluoromethyl enones via a zwitterionic intermediate (Scheme A, II) . However, the reactions were limited in the scope of α-alkyl diazoacetates (such as R = H, Me, and Et).…”
mentioning
confidence: 99%
“…Diazocarbonyl compounds have been versatile intermediates in diverse organic syntheses that can easily generate electron-deficient metal carbenes (Scheme A, I) in the presence of transition metal catalysts and further undergo a number of chemical transformations such as cyclopropanation, X–H (X = C, O, S, or N) insertion, ylide formation, and formal carbene dimerization . In addition, Lewis base catalysis was reported to promote (3+2) cycloaddition of nucleophilic diazocarbonyls activated by triphenylphosphine to react with β-trifluoromethyl enones via a zwitterionic intermediate (Scheme A, II) . However, the reactions were limited in the scope of α-alkyl diazoacetates (such as R = H, Me, and Et).…”
mentioning
confidence: 99%
“…4-trifluoromethylated-3,4,5-trisubstituted pyrazolines 181 a-c were synthesized by the use of ethyl diazoacetate in good to excellent yield as shown in scheme 49. [99] In addition, the authors have shown the synthetic feasibility of the developed method by using αsubstituted α-diazoacetates to synthesize the corresponding 4-trifluoromethylated-3,4,5,5-tetrasubstituted pyrazolines 181 d-f. The steric bulk of the diazoacetate was found to be significant in controlling the diastereoselectivity of the reaction.…”
Section: Pyrazole Derivativesmentioning
confidence: 99%
“…Considering this, recently, Liu and Zhang reported a phosphine catalysed synthesis of multi substituted 4‐(trifluoromethyl) pyrazolines from [3+2] cycloaddition of α ‐diazoacetates 180 and β ‐trifluoromethyl enones 3 . 4‐trifluoromethylated‐3,4,5‐trisubstituted pyrazolines 181 a – c were synthesized by the use of ethyl diazoacetate in good to excellent yield as shown in scheme 49 [99] …”
Section: Heterocyclic Synthesismentioning
confidence: 99%
“…Transition-metal-catalyzed olefin cyclopropanation using diazo compounds is a powerful strategy for the synthesis of optically active cyclopropanes. Our group has been committed to the research of diazo compounds . Therefore, we commenced our studies by gold-catalyzed asymmetric cyclopropanation of enamides with α-aryl diazoacetates as the source of the reactive metal carbenes, for the formation of multisubstituted cyclopropylamines bearing two to three contiguous stereogenic centers (Scheme c).…”
Section: Introdutionmentioning
confidence: 99%